The Relevance Of Trisakti Soekarno Concept With Nawacita In Jokowi-Jk Government - Mujahid Widian Saragih (Institute of Computer Science (IOCS), 2020)
This research describes the relevance of Trisakti Soekarno concept with Nawacita initiated by the government of Joko Widodo and Jusuf Kalla (Jokowi-JK). “The General Elections” in 2014 for Jokowi and JK as President and Vice President of Indonesia for 2014 to 2019 period. In the current government, Jokowi-JK uses the concept of Trisakti Sukarno as an ideological way Indonesia, which implemented into 9 priorities agenda of their government called Nawacita. Trisakti as the ideological base for Nawacita is interesting to look further considering the conceptual Trisakti built 50 years ago. What was the relevance and significance of Trisakti with Nawacita int this current government, become for this research. In condition to answer that, the conceptual framework of the Trisakti is used to see the relevance with Nawacita Jokowi-JK. The Conceptual framework is also used to find the significance of the concept of Trisakti with current conditions. The method used in this research is descriptive method with qualitative research. Data collection techniques in this study was conducted using the research library or library study to obtain data through documents. Relevance of Trisakti with Nawacita as a priority program can be seen from the similarity of identifying problems that are rooted in three factors namely political, economic and cultural. However, when analyzed in depth there are fundamental differences between Nawacita with Trisakti such differences rooted in the socio-political and not attached to the anti Nekolim character in Nawacita. The signification of Trisakti concept can be seen as an attempt to reoriented the fields of politics, economy and culture of Indonesia at this stage of the Indonesian revolution is lost. Significance Trisakti ultimately worth taking a look back when it was compared with the era of globalization and the current conditions.